Enantioselective Total Synthesis of (+)‐Neostenine. Issue 10 (2nd February 2016) - Nakayama, Yasuaki; Maeda, Yuichiro; Kotatsu, Masayuki; Sekiya, Ruriko; Ichiki, Masato; Sato, Takaaki; Chida, Noritaka
Abstract: A chirality transfer approach using acyclic polyol intermediates for the synthesis of (+)‐neostenine (1 ) has been developed. The sequential Overman/Claisen rearrangement of an allylic 1, 2‐diol was especially useful, installing two contiguous stereocenters with complete diastereoselectivity in a one‐pot sequence. The SmI2 ‐mediated cyclization and the subsequent chemoselective reduction of a lactam moiety accomplished the first enantioselective total synthesis of (+)‐neostenine (1 ). Abstract : 18 steps to alkaloid ! The first enantioselective total synthesis of (+)‐neostenine by a chirality transfer approach using three sigmatropic rearrangements of acyclic polyol intermediates has been reported (see scheme). The sequential Overman/Claisen rearrangement was especially useful to introduce two contiguous stereocenters, including a carbon–nitrogen bond. The reaction took place in a completely stereoselective fashion in a one‐pot sequence.